A digital twin-enhanced system for engineering product family design and optimization. (October 2020) - Lim, Kendrik Yan Hong; Zheng, Pai; Chen, Chun-Hsien; Huang, Lihui
Highlights: A proposed digital twin reference model for product family design and optimization. Context-aware engineering solution generation and reconfiguration. Knowledge graph-based decision-making capabilities. Digital twin-enhanced tower crane product family management. Abstract: Engineering product family design and optimization in complex environments has been a major bottleneck in today's industrial transformation towards smart manufacturing. Digital twin (DT), as a core part of cyber-physical system (CPS), can provide decision support to enhance engineering product lifecycle management workflows via remote monitoring and control, high-fidelity simulation, and solution generation functionalities. Although many studies have proven DT to be highly suited for industry needs, little has been reported on the product family design and optimization capabilities specifically with context awareness, which could be leaving many enterprises ambivalent on its adoption. To fill this gap, a reusable and transparent DT capable of situational recognition and self-correction is essentially required. This paper develops a generic DT architecture reference model to enable the context-aware product family design optimization process in a cost-effective manner. A case study featuring asset re-/configuration within a dynamic environment is further described to demonstrate its in-context decision-aiding capabilities. The authors hope this study can provide valuable insights to both academia and industry in improving their engineering product family management process.